Improving clinical nursing education in South of Iran 2016‒2021: A cooperative action research study - Hojat, M. (South African Journal of Higher Education, 2024)
Clinical education is a heart of education. The improvement of it is a challenge for every university. African countries like Iran are developing, especially in higher education. So the work context is almost the same. The present study was conducted to identify the clinical education challenges and improving it by a cooperative action research approach. This study was conducted from 2016 to 2021. The participants were 41 nurses and head nurses, 86 nursing students, and 26 nursing teachers. They worked through two cycles of reflection for 50 months. The data were collected and analyzed using the qualitative and quantitative methods. The findings of the qualitative data by 11 semi-structured interviews and ten focus group discussion revealed that the 8 sub-categories (lack of attention to the evaluation process, non-participatory evaluation, low-staff educational cooperation, ineffective trainer, non-educational clinical context, student educational disability, student drowning in bed, non-planning Participatory) and 3 main themes (planning challenges, implementing challenges and evaluation challenges) were obtained. After change in planning and implementation process, evaluation was done by a standard researcher made questionnaire according to the sub-categories of qualitative data. That showed satisfaction Improvement in 3 main themes in two cycle (planning, implementing, and evaluating). Reflection in every cycle caused change in planning, implementing and evaluating process. Moreover, it caused learning for all participants. These participants made a small change in the style of educational management from authoritarian to participatory. So, run programs introduced in this action research could be applicable for educational managers and policymakers.